Expressions of miR-302a, miR-105, and miR-888 Play Critical Roles in Pathogenesis, Radiotherapy, and Prognosis on Rectal Cancer Patients: A Study From Rectal Cancer Patients in a Swedish Rectal Cancer Trial of Preoperative Radiotherapy to Big Database Analyses - Meng, Wen-Jian; Pathak, Surajit; Zhang, Xueli; Adell, Gunnar; Jarlsfelt, Ingvar; Holmlund, Birgitta; Wang, Zi-Qiang; Zhang, Alexander S.; Zhang, Hong; Zhou, Zong-Guang; Sun, Xiao-Feng (Frontiers in Oncology, 2020)
Differential expressions and functions of various micoRNAs (miRNAs) have been intensively studied in both colon and rectal cancers. However, the importance of miRNAs on radiotherapy (RT) response and clinical outcome in rectal cancer patients remain unclear. In this study, we used real-time PCR to examine the expressions of miR-302a, miR-105 and miR-888 in normal mucosa and cancer tissues from rectal cancer patients with and without preoperative RT. The biological function of miR-302a, miR-105 and miR-888 expression was further analyzed and identified through the public databases: TCGA (The Cancer Genome Atlas) and GEPIA (Gene Expression Profiling Interactive Analysis). The results showed that expression of miR-105 in rectal cancer was higher than that in normal mucosa in RT (P=0.042) and non-RT patients (P=0.003), which was associated with mucinous histological type (P=0.004), COX-2 (P=0.042) and p73 expression (P=0.030). Expression of miR-302a was showed more frequency in cancers with necrosis (P=0.033) and with WRAP53 expression (P=0.015), whereas miR-888 expression occurred more frequently in tumors with protein expression of survivin (P=0.015), AEG-1 (P=0.003) and SATB1 (P=0.036). Moreover, TargetScan also predicted AEG-1 and SATB1 as putative targets for miR-888. The miRNA-gene network analysis showed that ABI2 was associated with all the three miRNAs, with lower expression and good diagnostic value in rectal cancers. TCGA database demonstrated the association of miR-105 expression with high CEA level (P=0.048). RT reduced the expressions of miR-302a, miR-105 and miR-888. Prognostic analysis showed that miR-888 expression was independently associated with worse survival of patients without RT (OS, P=0.001; DFS, P=0.009). Analysis of biological function revealed that the protein serine/threonine kinase activity and PI3K-AKT signaling pathway were the most significant enriched functions and pathways, respectively. Our findings suggest that miR-105 is involved in rectal cancer pathogenesis and miR-888 is associated with prognosis. miR-302a, miR-105, and miR-888 have potential influence on the pathogenesis, radiotherapy and prognosis of rectal cancer.